Fibrosis of mesothelial cell-induced peritoneal implantation of ovarian cancer cells - Wang J; Liu C; Chang X; Qi Y; Zhu Z; Yang X (Cancer Management and Research, 2018)
Jinou Wang,1 Chang Liu,1 Xiaoying Chang,1 Yafei Qi,1 Zhi Zhu,2 Xianghong Yang1 1Department of Pathology, Shengjing Hospital of China Medical University, Shenyang, China; 2Department of Surgical Oncology, The First Hospital of China Medical University, Shenyang, China Background: Peritoneal metastasis frequently occurs in patients with advanced ovarian cancer and is the main basis for a poor prognosis. The mechanism underlying preferential ovarian cancer spread to the peritoneum is not well understood. Methods: Herein, we investigated the significance and mechanism underlying fibrosis of mesothelial cells promoting peritoneal implantation of ovarian cancer. We have assessed the mesothelial cell fibroblast transformation process in peritoneal tissues of omentum and fibrotic mesothelial cell release of chemokines to promote dissemination by scanning electron microscopy, ELISA, Western blot, and Transwell chamber assay. Results: We showed that the fibrosis of mesothelial cells exists in the peritoneum of ovarian cancer patients with peritoneal metastasis. Fibrosis of the mesothelial cells was induced by TGF-β1, which upregulates the CXCL12–CXCR4 and CXCL16–CXCR6 axes of mesothelial cells. Conclusion: CXCL12–CXCR4 and CXCL16–CXCR6 may be important signaling pathways closely involved in peritoneal metastasis of ovarian cancer that require further investigation. The findings may lead to developing alternative strategies aimed at preventing and treating the metastasis of ovarian cancer. Keywords: ovarian cancer, peritoneal, mesothelial cell, fibrosis